SHARIA MARKETING STRATEGY FOR MICRO, SMALL AND MEDIUM ENTERPRISES (MSMEs) IN THE RELIGIOUS TOURISM SECTOR - Mashuri, Nailul; Hidayatullah, Indra; Farid, Muhammad (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
Sharia marketing is not merely a theoretical concept, but rather a business practice based on Islamic values, emphasizing theistic, ethical, and humanistic principles. In its application, Sharia marketing focuses on Islamic values to prevent business actors from prohibited practices, such as usury and other transactions that can undermine market morality. This concept emphasizes the importance of ethics, honesty, transparency, and fairness in every transaction. Furthermore, Sharia marketing also provides new insights for the public regarding the application of Islamic values in the business world, thereby creating a more moral, fair, and beneficial trading system for all parties. The focus of this research is how the Sharia marketing strategies of MSMEs in religious tourism increase revenue. The purpose of this paper is to provide an understanding of the Sharia marketing strategies of MSMEs in the religious tourism sector to increase revenue. This research uses a descriptive qualitative method with a case study approach. The results show that MSMEs apply Sharia principles through honesty in transactions, friendly service, and maintaining product quality. The marketing strategies employed include a personal approach through word-of-mouth communication, social media utilization, and the use of digital payment systems. Implementing these principles and strategies has been proven to increase consumer trust and directly impact business revenue.